HUBUNGAN ANTARA PPE, WPS, BBS DAN KOMPETENSI WELDER TERHADAP PENERAPAN K3 BIDANG PEKERJAAN FABRIKASI LOGAM PADA PROSES WELDING - Makomulamin; Nila Puspita Sari; Alfina Mutiara Sany (Institut Kesehatan dan Teknologi Al Insyirah, 2024)
Welding is a high-risk job due to involving heat and electricity. To ensure the safety of workers at CV. Bengkel Las Adi Jaya, it is crucial to pay attention to the use of Personal Protective Equipment (PPE), the implementation of Welding Procedure Standard (WPS), Behavior Based Safety (BBS), and the competence of welders. This study aims to determine the correlation between the effectiveness of using Personal Protective Equipment (PPE), Welding Procedure Standard (WPS) specifications, Behavior Based Safety (BBS), and welder competence with the implementation of Occupational Safety and Health (OSH) in the welding process at Bengkel Las Adi Jaya. This is a quantitative analytical method with a cross-sectional design. The results showed a significant correlation between the effectiveness of using Personal Protective Equipment (PPE) with a p-value of 0.041, the implementation of WPS with compliance with OSH practices with a p-value of 0.000, and Welder Competence with a p-value of 0.039. However, no significant relationship was found between behavior-based safety (BBS) and OSH compliance. This study highlights the important role of technical factors such as PPE, WPS, and Welder Competence in ensuring workplace safety. This study recommends increasing the use of PPE, strict adherence to WPS, and continuous skill improvement for welders to create a safer working environment